The Siginificance of Pancasila Education Subject in Building the Character of STMIK STIKOM Indonesia Students - Ni Putu Suci Meinarni; Ni Putu Yeny Nirmalasari; Ni Putu Candra Eka Susanti; Ida Bagus Satriya Wibawa; Komang Ari Prasetia (Badan Riset dan Inovasi Daerah Provinsi Bali, 2021)
Purpose: This study aims to determine the opinions of students about the importance of Pancasila Education subject in shaping student character at STMIK STIKOM Indonesia. Research method: The type of research chosen is qualitative research. The data collection technique chosen was a questionnaire with more than 300 students as respondents. Data assessment was carried out starting from data collection, data reduction, data description and decision making. Results and discussion: Pancasila covers a mindset that is in accordance with the national culture. Pancasila Education within the scope of the STMIK STIKOM Indonesia campus certainly affects the mindset of students in responding to various problems at this time. Implication: The method of learning Pancasila Education which is more popular is the technique of discussion and lectures, to help students understand the material. Therefore, Pancasila Education is expected to be able to increase knowledge and practice of Pancasila teachings in everyday life.